Lithium carbon fluoride battery
By adding double bond silane and boric acid ester to the electrolyte of Li/CFx battery, forming a passivation layer and complexing free fluorine, the electrolyte decomposition problem caused by the instability of fluoride is solved, and the storage stability of lithium fluoride carbon batteries is significantly improved.
Patent Information
- Application Number
- CN202411815140.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
The instability of carbon fluoride in Li/CFx batteries leads to the decomposition of the electrolyte, affecting the storage stability of the battery. The existing coating methods are complex and costly, and the problem cannot be solved from the root cause.
The double-bonded silane compound and borate ester additive are added to the electrolyte solution. The double-bonded silane forms a passivation layer to block the contact between the electrolyte solution and the fluorinated carbon, and the borate esters complexing free fluorine to improve the stability of the electrolyte.
Significantly improve the stability of carbon fluoride and negative electrodes, enhance the stability and conductivity of the electrolyte, improve the interface characteristics of the electrode/electrolyte, and improve the storage stability of lithium fluoride carbon batteries.
Smart Images

Figure CN119725589A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a lithium carbon fluoride battery. Background Art
[0002] Li / CFx battery is the type of lithium battery with the highest energy density at present. Compared with other primary batteries, the theoretical specific energy value of Li / CFx battery can reach up to 2180Wh / kg. At the same time, Li / CFx battery also has the characteristics of stable discharge voltage, high safety and environmental friendliness. It is particularly suitable as a power source for instrument equipment used in unmanned or closed environments, such as missile ignition systems, underwater electronic detectors, radio transmitters, pacemakers, etc.
[0003] However, there are some unstable carbon-fluorine bonds in the positive active material carbon fluoride in Li / CFx batteries. Under high temperature or long-term storage, these unstable carbon-fluorine bonds will undergo homolytic or heterolytic cleavage to form carbon free radicals, fluorine free radicals or carbon cations, fluoride ions, which have high chemical activity and will cause the electrolyte to decompose and lead to rapid capacity decay of the battery, which will greatly affect the storage stability of Li / CFx batteries.
[0004] At present, the main means to improve the stability of carbon fluoride in the electrolyte is to set a coating layer on the surface of carbon fluoride, and use the coating layer to block the direct contact between carbon fluoride and the electrolyte to alleviate the side reaction between carbon fluoride and the electrolyte, thereby improving the storage stability of Li / CFx batteries. However, the preparation process of coated carbon fluoride is complicated, costly and not conducive to large-scale production. It not only reduces the conductivity of carbon fluoride materials, but also cannot solve the problem of side reactions between carbon fluoride and electrolyte from the root. Summary of the invention
[0005] In order to improve the stability of carbon fluoride and inhibit the reaction between electrolyte and carbon fluoride, thereby enhancing the storage stability of lithium carbon fluoride batteries, the present application provides a lithium carbon fluoride battery.
[0006] The present application provides a lithium carbon fluoride battery, which adopts the following technical solution:
[0007] A lithium carbon fluoride battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte;
[0008] The positive electrode sheet includes a positive electrode active material layer containing a positive electrode active material, and the positive electrode active material includes a fluorinated carbon material;
[0009] The electrolyte includes an additive, wherein the additive includes a first additive and a second additive;
[0010] The first additive comprises a double bond silane compound, the chemical formula of which is R 1b Si a R 2 2a+2-b ; Wherein, a is an integer from 1 to 2, b is an integer from 1 to 6, R 1 is at least one of vinyl, propenyl and butenyl, R 2 is at least one of methyl, ethyl, and butyl;
[0011] The second additive is a borate additive.
[0012] The present application introduces a first additive and a second additive into the electrolyte, and the double-bonded silane in the first additive can undergo free radical polymerization or ion polymerization under the action of carbon cations / carbon radicals, thereby forming a passivation layer on the surface of the positive electrode, which can block the contact between the electrolyte and the carbon fluoride, and at the same time, it can also form a stable passivation layer on the surface of the metallic lithium, further inhibiting the decomposition of the electrolyte at the positive and negative electrodes and avoiding the decomposition of the electrolyte, thereby significantly improving the stability of the carbon fluoride and the negative electrode; at the same time, the electron-deficient boric acid ester in the second additive can complex the free fluorine generated by the decomposition of the carbon-fluorine bond in the carbon fluoride material, thereby helping to improve the stability of the electrolyte, and then improve the stability of the carbon fluoride; and the boric acid ester in the second additive can improve the conductivity of the electrolyte, promote the use of the carbon fluoride capacity, and improve the interface characteristics of the electrode / electrolyte; all of which help to improve the storage stability of the lithium carbon fluoride battery, and there is no need to use a coating method to coat the carbon fluoride material, so that the carbon fluoride material can still exert good conductivity.
[0013] Therefore, the present invention effectively improves the stability of the positive and negative electrodes and the electrolyte through the synergistic effect of silane containing alkenyl double bonds and silane containing alkoxy groups, thereby achieving the improvement of the long-term and high-temperature storage stability of the lithium carbon fluoride battery.
[0014] Preferably, the first additive includes at least one of vinyltrimethylsilane, vinyltriethylsilane, divinyltetramethyldisilane, divinyldimethylsilane, divinyldipropylsilane, trivinylmethylsilane, trivinylethylsilane, tetravinylsilane and tetraallylsilane.
[0015] Preferably, the second additive comprises at least one of trimethyl borate, triethyl borate, tripropyl borate, tributyl borate, tri(trimethylsilyl)borate, tri(triethylsilyl)borate, tri(2,2,2-trifluoroethyl)borate, tri(hexafluoroisopropyl)borate, triphenylborate, tri(pentafluorophenyl)borate, tripropargyl borate, (di-n-butyl)(vinyl)borate, and (di-n-butyl)(propargyl)borate.
[0016] Preferably, the additive accounts for 0.1%-10% by mass in the electrolyte.
[0017] By controlling the mass proportion of the additive in the electrolyte to meet the above range of values, the stability of the electrolyte can be improved, the interface characteristics of the electrode / electrolyte can be improved, and the storage stability of the lithium carbon fluoride battery can be improved on the basis of ensuring that the carbon fluoride capacity is fully utilized. When the mass proportion of the additive in the electrolyte is too low, the stability of the electrolyte and the stability of the carbon fluoride cannot be improved, which will be detrimental to the improvement of the storage performance of the lithium carbon fluoride battery; when the mass proportion of the additive in the electrolyte is too high, it will have an adverse effect on the carbon fluoride film formation. Excessive additive content may change the structure and properties of the carbon fluoride film, resulting in the film uniformity, stability or functionality being affected, which is also detrimental to the improvement of the storage performance of the lithium carbon fluoride battery.
[0018] Preferably, the mass proportion of the first additive in the electrolyte is 0.1%-10%; the mass proportion of the second additive in the electrolyte is 0.1%-5%.
[0019] Preferably, the mass proportion of the first additive in the electrolyte is 0.1%-5%; the mass proportion of the second additive in the electrolyte is 0.1%-2%.
[0020] By controlling the mass proportion of the first additive and the mass proportion of the second additive in the electrolyte, the two can cooperate to not only strengthen the protective effect of the passivation layer on the positive and negative electrodes and prevent the positive and negative electrodes from decomposing in the electrolyte, but also improve the stability of the electrolyte, which helps to improve the stability of the electrode / electrolyte interface, thereby significantly improving the high-temperature storage stability of the lithium carbon fluoride battery. The proportion of the first additive and the second additive meets the above range of values, which can not only avoid the situation where the excessive amount of the first additive has an adverse effect on the electrolyte turbidity and causes an increase in the impedance of the lithium carbon fluoride battery, but also avoid the excessive amount of the second additive from corroding the lithium negative electrode.
[0021] Preferably, the electrolyte further comprises an organic solvent and a lithium salt.
[0022] Preferably, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium trifluoromethanesulfonate, lithium bis(oxalatoborate) or bis(fluorooxalatoborate); and the concentration of the lithium salt in the electrolyte is 0.5-2 mol / L.
[0023] By introducing lithium salts into the electrolyte, on the one hand, the loss of active lithium during the cycle of lithium carbon fluoride batteries can be compensated, and on the other hand, the ion conductivity of the electrolyte can be increased, thereby promoting the use of carbon fluoride capacity and improving the interface properties of the electrode / electrolyte.
[0024] Preferably, the organic solvent includes at least one of ethylene glycol dimethyl ether, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and gamma-martinolactone.
[0025] The organic solvent in the present application can promote the dissolution of lithium salt, optimize the overall composition of the electrolyte, improve the conductivity of the electrolyte, and reduce polarization.
[0026] Preferably, the positive electrode fluorinated carbon material includes at least one of fluorinated graphite, fluorinated hard carbon material, and fluorinated soft carbon material.
[0027] Preferably, the compaction density of the positive electrode sheet is 1.23-1.29 g / cm 3 The porosity of the positive electrode sheet is 48%-52%.
[0028] By controlling the compaction density and porosity of the positive electrode sheet, it helps to increase the ion conduction rate, increase the insertion and extraction rate of lithium ions in the positive electrode, and is beneficial to the performance of the carbon fluoride capacity.
[0029] Preferably, the total thickness of the positive electrode active material layer is 98-102 μm.
[0030] Preferably, the negative electrode sheet comprises a lithium-containing material.
[0031] Preferably, the negative electrode sheet comprises a lithium sheet, and the thickness of the lithium sheet is 47-53 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a discharge curve diagram of the lithium battery in Example 1 before and after storage.
[0033] Figure 2 This is a discharge curve diagram of the lithium battery in Comparative Example 1 before and after storage. DETAILED DESCRIPTION
[0034] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0036] Unless otherwise indicated, all numerical values expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.
[0037] As used herein, "and / or" means one or all of the mentioned elements.
[0038] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.
[0039] All percentages in this application are by weight unless otherwise stated.
[0040] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.
[0041] Example 1
[0042] 1. Preparation of electrolyte
[0043] In a glove box filled with argon, propylene carbonate PC and ethylene glycol dimethyl ether DME are mixed in a mass ratio of 1:1, and then lithium salt (lithium perchlorate LiClO4), a first additive (tetravinylsilane) and a second additive (trimethyl borate) are added thereto, and the electrolyte is obtained after stirring evenly; wherein the concentration of LiClO4 is 1 mol / L, the content of tetravinylsilane is 1wt%, and the content of trimethyl borate is 0.5wt%.
[0044] 2. Preparation of carbon fluoride positive electrode
[0045] The carbon fluoride active material (graphite fluoride), the conductive agent (carbon black) and the binder (polyvinylidene fluoride) were mixed in a mass ratio of 87:8:5 to prepare a positive electrode slurry with a viscosity of 12000cp;
[0046] The positive electrode slurry was coated once on the A side of the carbon-coated aluminum foil, and then coated again on the B side of the carbon-coated aluminum foil; the positive electrode sheet with a loading of 120 g / m 2 After coating, it was dried at 100°C and rolled to obtain a compacted density of 1.23 g / cm 3 , a positive electrode sheet having a porosity of 52% and a total thickness of the positive electrode active material layer of 98 μm; cutting or die-cutting into corresponding sizes to obtain a carbon fluoride positive electrode sheet;
[0047] 3. Negative electrode preparation
[0048] The lithium ribbon was cut into corresponding sizes to obtain a lithium sheet with a thickness of 47 μm as a negative electrode sheet.
[0049] 4. Lithium Carbon Fluoride Battery Preparation
[0050] The carbon fluoride positive electrode sheet, the metal lithium negative electrode sheet and the separator are assembled into a battery cell, the electrolyte is injected into the battery cell with an injection coefficient of 1.3 g / Ah, and a lithium carbon fluoride battery is obtained after sealing.
[0051] The discharge curve of the lithium fluoride carbon battery before and after storage in this embodiment is as follows: Figure 1 shown.
[0052] Example 2
[0053] 1. Preparation of electrolyte
[0054] In a glove box filled with argon, 1,4-butyrolactone GBL and ethylene glycol dimethyl ether DME were mixed in a mass ratio of 1:1, and then lithium salt LiBF4, a first additive (divinyldimethylsilane), and a second additive (triphenylborate) were added thereto. The electrolyte was obtained after stirring evenly; the LiBF4 concentration was 1 mol / L, the divinyldimethylsilane content was 2 wt%, and the triphenylborate content was 1 wt%.
[0055] 2. Preparation of carbon fluoride positive electrode
[0056] The carbon fluoride active material (fluorinated hard carbon), the conductive agent (conductive carbon black) and the binder (polyvinylidene fluoride) were mixed in a mass ratio of 87:8:5 to prepare a positive electrode slurry with a viscosity of 12000cp;
[0057] The positive electrode slurry was coated once on the A side of the carbon-coated aluminum foil, and then coated again on the B side of the carbon-coated aluminum foil; the positive electrode sheet with a loading of 120 g / m 2 After coating, it was dried at 100°C and rolled to obtain a compacted density of 1.29 g / cm 3 , a positive electrode sheet having a porosity of 48% and a total thickness of the positive electrode active material layer of 102 μm; cutting or die-cutting into corresponding sizes to obtain a fluorinated carbon positive electrode sheet;
[0058] 3. Negative electrode preparation
[0059] The lithium ribbon was cut into corresponding sizes to obtain a lithium sheet with a thickness of 53 μm as a negative electrode sheet.
[0060] 4. Lithium Carbon Fluoride Battery Preparation
[0061] The carbon fluoride positive electrode sheet, the metal lithium negative electrode sheet and the separator are assembled into a battery cell, the electrolyte is injected into the battery cell with an injection coefficient of 1.0 g / Ah, and a lithium carbon fluoride battery is obtained after sealing.
[0062] Example 3
[0063] 1. Preparation of electrolyte
[0064] In a glove box filled with argon, propylene carbonate PC and ethylene glycol dimethyl ether DME were mixed in a mass ratio of 1:1, and then lithium bis(trifluorosulfonyl)imide LiFSi and lithium perchlorate LiClO4, a first additive (trivinylmethylsilane), and a second additive (tris(trimethylsilyl)borate) were added thereto, and the electrolyte was obtained after stirring evenly; wherein the concentration of LiFSi was 0.8 mol / L, the concentration of LiClO4 was 0.5 mol / L, the content of trivinylmethylsilane was 2 wt%, and the content of tris(trimethylsilyl)borate was 1.5 wt%.
[0065] 2. Preparation of carbon fluoride positive electrode
[0066] The carbon fluoride active material (fluorinated soft carbon), the conductive agent (conductive carbon black) and the binder (polyvinylidene fluoride) were mixed in a mass ratio of 87:8:5 to prepare a positive electrode slurry with a viscosity of 12000cp;
[0067] The positive electrode slurry was coated once on the A side of the carbon-coated aluminum foil, and then coated again on the B side of the carbon-coated aluminum foil; the positive electrode sheet with a loading of 120 g / m 2 After coating, it was dried at 100°C and rolled to obtain a compacted density of 1.26 g / cm 3 , a positive electrode sheet having a porosity of 50% and a total thickness of the positive electrode active material layer of 100 μm; cutting or die-cutting into corresponding sizes to obtain a carbon fluoride positive electrode sheet;
[0068] 3. Negative electrode preparation
[0069] The lithium ribbon was cut into corresponding sizes to obtain a lithium sheet with a thickness of 50 μm as a negative electrode sheet.
[0070] 4. Lithium Carbon Fluoride Battery Preparation
[0071] The carbon fluoride positive electrode sheet, the metal lithium negative electrode sheet and the separator are assembled into a battery cell, the electrolyte is injected into the battery cell with an injection coefficient of 1.1 g / Ah, and a lithium carbon fluoride battery is obtained after sealing.
[0072] Example 4
[0073] The difference between this embodiment and embodiment 1 is that the first additive in the electrolyte is trivinylethylsilane, the second additive is tri(hexafluoroisopropyl)borate, the content of trivinylethylsilane is 1.5wt%, and the content of tri(hexafluoroisopropyl)borate is 0.5wt%; other steps and parameter settings are consistent with embodiment 1.
[0074] Example 5
[0075] The difference between this embodiment and embodiment 1 is that the first additive in the electrolyte is divinyldimethylsilane, and the second additive is tri(triethylsilyl) borate; the content of divinyldimethylsilane is 7wt%, and the content of tri(triethylsilyl) borate is 3wt%; the other steps and parameter settings are consistent with embodiment 1.
[0076] Example 6
[0077] The difference between this embodiment and embodiment 1 is that the content of tetravinylsilane, the first additive of the electrolyte, is changed from 1wt% to 0.03wt%; the other steps and parameter settings are consistent with those of embodiment 1.
[0078] Example 7
[0079] The difference between this embodiment and embodiment 1 is that the content of tetravinylsilane, the first additive of the electrolyte, is changed from 1wt% to 3wt%; the other steps and parameter settings are consistent with those of embodiment 1.
[0080] Example 8
[0081] The difference between this embodiment and embodiment 1 is that the content of trimethyl borate, the second additive of the electrolyte, is changed from 0.5wt% to 0.05wt%; the other steps and parameter settings are consistent with those of embodiment 1.
[0082] Example 9
[0083] The difference between this embodiment and embodiment 1 is that the content of trimethyl borate, the second additive of the electrolyte, is changed from 0.5wt% to 2wt%; the other steps and parameter settings are consistent with those of embodiment 1.
[0084] Comparative Example 1
[0085] The difference between this comparative example and Example 1 is that the electrolyte does not contain the first additive and the second additive; other steps and parameter settings are consistent with Example 1.
[0086] The discharge curve of the lithium fluoride carbon battery before and after storage in this comparative example is as follows Figure 2 shown.
[0087] Comparative Example 2
[0088] The difference between this comparative example and Example 2 is that the electrolyte does not contain the first additive and the second additive; the other steps and parameter settings are consistent with Example 2.
[0089] Comparative Example 3
[0090] The difference between this comparative example and Example 3 is that the electrolyte does not contain the first additive and the second additive; the other steps and parameter settings are consistent with Example 3.
[0091] Comparative Example 4
[0092] The difference between this comparative example and Example 1 is that the first additive of equal weight is used to replace the second additive, and the electrolyte contains only the first additive; the other steps and parameter settings are consistent with Example 1.
[0093] Comparative Example 5
[0094] The difference between this comparative example and Example 1 is that the second additive of equal weight is used to replace the first additive, and the electrolyte contains only the second additive; the other steps and parameter settings are consistent with Example 1.
[0095] Test Method
[0096] 1. Storage stability test
[0097] The storage stability test of the lithium carbon fluoride batteries in the above embodiments and comparative examples is carried out, and the specific test method is as follows: (1) the lithium / carbon fluoride battery is discharged at room temperature at 0.01C, and the discharge cut-off voltage is 1.5V, and the discharge capacity and internal resistance R1 of the new battery are recorded; (2) a new lithium carbon fluoride battery of the same type is placed in a 70°C oven and stored for 1 month, and then tested under the above conditions and the discharge capacity and internal resistance R2 of the battery after high temperature storage are recorded;
[0098] Discharge capacity retention rate = discharge capacity of battery after high temperature storage / discharge capacity of new battery × 100%; internal resistance growth rate = (internal resistance R2 after storage - internal resistance R1 before storage) / internal resistance R1 before storage × 100%;
[0099] Table 1
[0100]
[0101]
[0102] In combination with Examples 1-3, Comparative Examples 1, 4-5 and Table 1, it can be seen that by adding the first additive and the second additive to the electrolyte, the double bond silane can generate a passivation layer with stable performance and dense structure on the surface of the carbon fluoride positive electrode active material and the metallic lithium, isolating the contact between the electrolyte and the carbon fluoride positive electrode active material and the negative electrode lithium sheet, while the borate ester can complex the free fluorine in the electrolyte, thereby improving the stability of the electrolyte; the combination of the two can improve the interface characteristics of the electrode / electrolyte, thereby significantly improving the storage stability of the lithium carbon fluoride battery, so that the lithium carbon fluoride battery still maintains a high capacity retention rate and a low internal resistance growth rate after long-term storage at high temperature.
[0103] In combination with Examples 1-3, Comparative Examples 1-3 and Table 1, it can be seen that the combination of the first additive and the second additive can improve the storage stability of graphite fluoride, fluorinated hard carbon and fluorinated soft carbon batteries. The solution provided in the present application is universal for lithium carbon fluoride batteries using different carbon fluoride materials.
[0104] Combining Example 1, Examples 4-5 and Table 1, it can be seen that the combination of different vinyl silane additives and borate ester additives can improve the storage stability of lithium fluorinated carbon.
[0105] In combination with Example 1, Examples 6-7 and Table 1, it can be seen that the change in the content of the first additive in the electrolyte has a significant effect on the storage stability of the battery cell; when the content of the first additive is low, it cannot play a good passivation role on the metallic lithium, and it cannot cooperate with the second additive to achieve the improvement of the stability of the electrode-electrode liquid interface, so that the capacity retention rate of the lithium fluoride carbon battery after long-term storage at high temperature is slightly reduced; when the content of the first additive is too high, the turbidity of the electrolyte will increase, and the impedance of the battery cell will increase significantly, so that the capacity retention rate of the lithium fluoride carbon battery after long-term storage at high temperature is significantly reduced;
[0106] In combination with Example 1 and Examples 8-9 and Table 1, it can be seen that the change in the content of the second additive in the electrolyte has a significant effect on the storage stability of the battery cell; when the content of the second additive is too little, the free fluorine generated by the storage of the carbon fluoride material in the electrolyte cannot be removed, and the storage stability of the battery cell is limited, causing the capacity retention rate of the lithium carbon fluoride battery to slightly decrease after long-term storage at high temperature; when the content of the second additive is too high, the alkoxysilane in the second additive will corrode the metallic lithium, causing the storage stability of the battery cell to decrease, causing the capacity retention rate of the lithium carbon fluoride battery to significantly decrease after long-term storage at high temperature. In summary, the combination of vinyl silane and borate ester significantly improves the storage stability of lithium carbon fluoride batteries.
[0107] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.
Claims
1. A lithium carbon fluoride battery, characterized in that: Including positive electrode sheet, negative electrode sheet and electrolyte; The positive electrode sheet includes a positive electrode active material layer containing a positive electrode active material, and the positive electrode active material includes a fluorinated carbon material; The electrolyte includes an additive, wherein the additive includes a first additive and a second additive; The first additive comprises a double bond silane compound, the chemical formula of which is R 1 b Si a R 2 2a+2-b ; Wherein, a is an integer from 1 to 2, b is an integer from 1 to 6, R 1 is at least one of vinyl, propenyl and butenyl, R 2 is at least one of methyl, ethyl, and butyl; The second additive is a borate additive.
2. The lithium carbon fluoride battery according to claim 1, characterized in that: The first additive includes at least one of vinyltrimethylsilane, vinyltriethylsilane, divinyltetramethyldisilane, divinyldimethylsilane, divinyldipropylsilane, trivinylmethylsilane, trivinylethylsilane, tetravinylsilane, and tetraallylsilane.
3. The lithium carbon fluoride battery according to claim 1, characterized in that: The second additive includes at least one of trimethyl borate, triethyl borate, tripropyl borate, tributyl borate, tri(trimethylsilyl)borate, tri(triethylsilyl)borate, tri(2,2,2-trifluoroethyl)borate, tri(hexafluoroisopropyl)borate, triphenylborate, tri(pentafluorophenyl)borate, tripropargyl borate, (di-n-butyl)(vinyl)borate, and (di-n-butyl)(propargyl)borate.
4. The lithium carbon fluoride battery according to claim 1, characterized in that: The additive accounts for 0.1%-10% by mass in the electrolyte.
5. The lithium carbon fluoride battery according to claim 1, characterized in that: The mass proportion of the first additive in the electrolyte is 0.1%-10%; the mass proportion of the second additive in the electrolyte is 0.1%-5%.
6. The lithium carbon fluoride battery according to claim 1, characterized in that: The electrolyte also includes an organic solvent and a lithium salt.
7. The lithium carbon fluoride battery according to claim 6, characterized in that: The lithium salt comprises at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium trifluoromethanesulfonate, lithium bis(oxalatoborate) or bis(fluorooxalatoborate); Preferably, the concentration of the lithium salt in the electrolyte is 0.5-2 mol / L.
8. The lithium carbon fluoride battery according to claim 6, characterized in that: The organic solvent includes at least one of ethylene glycol dimethyl ether, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and gamma-martinolactone.
9. The lithium carbon fluoride battery according to claim 1, characterized in that: The positive electrode fluorinated carbon material includes at least one of fluorinated graphite, fluorinated hard carbon material, and fluorinated soft carbon material.
10. The lithium carbon fluoride battery according to claim 1, characterized in that: The compaction density of the positive electrode sheet is 1.23-1.29 g / cm 3 The porosity of the positive electrode sheet is 48%-52%.
11. The lithium carbon fluoride battery according to claim 1, characterized in that: The total thickness of the positive electrode active material layer is 98-102 μm.
12. The lithium carbon fluoride battery according to any one of claims 1 to 11, characterized in that: The negative electrode sheet includes a lithium-containing material.